Photocurrent Enhancement by Spontaneous Formation of a p–n Junction in Calcium‐Doped Bismuth Vanadate Photoelectrodes. Issue 10 (30th May 2018) - Abdi, Fatwa F.; Starr, David E.; Ahmet, Ibbi Y.; van de Krol, Roel
Abstract: The application of bismuth vanadate (BiVO4 ) photoelectrodes for solar water splitting is hindered by the poor carrier transport. To overcome this, multiple donor‐doping strategies (e.g. dual doping, gradient doping) have been explored. Here, we show for the first time the successful introduction of calcium (Ca) as an acceptor‐type dopant into BiVO4 photoelectrodes. Interestingly, instead of generating cathodic photocurrents, the Ca‐doped BiVO4 photoelectrodes show anodic photocurrents with an enhanced carrier separation efficiency. Hard X‐ray photoelectron spectroscopy (HAXPES) shows that this enhancement is caused by out‐diffusion of Ca during the deposition process, which spontaneously creates a p–n junction within the BiVO4 layer. Overall, a significant two‐fold improvement of the AM1.5 photocurrent is obtained upon Ca‐doping. This study highlights the importance of controlled doping beyond simply modifying carrier concentration and may enable new device architectures in photoelectrode materials. Abstract : Dopant diffusion : Poor carrier separation represents one of the major limitations in the development of metal oxide photoelectrodes. Introducing Ca as an acceptor‐type dopant in BiVO4 photoelectrodes spontaneously creates a p–n junction in the film due to Ca outdiffusion (see figure). As a result, the charge carrier separation is enhanced, and the AM1.5 photocurrent is improved by a factor of two.